Some thoughts on the role of the Vietnamese state in the process of shifting to the market economy - Tai, Tran Anh (VNU Journal of Science: Legal Studies, 2004)
Nowadays, in the world, there are many different economic operation models at varying levels of success. Yet there is no model that operates without the State’s interference. A strong and intelligent state is one of the determinants for the success of an economic operation model.